Enhanced levels of hazardous trace elements (Cd, Cu, Pb, Se, Zn) in bird tissues in the context of environmental pollution by Raša coal (Rudarsko-geološko-naftni zbornik, 2022)
The mining and burning of Croatian Raša coal had resulted in release of various contaminants into the local environment. They have remained in the local soil, water, and plants, and became available to animals through their consumption. In this study, tissue samples from a total of 12 birds from the Raša area and 8 birds from a control area were subjected to multi-element analysis (Al, V, Cr, Mn, Fe, Co, Cu, Zn, As, Se, Mo, Cd, Pb) by ICP-MS. The obtained results showed increased Se and Cd concentrations in some bird tissue samples compared to the control area. The highest concentrations of Cu, Zn, and Se were found in the liver, while the highest concentrations of Cd and Pb were found in the kidneys. Although some hazardous trace elements were elevated in the tissues of game species, the risk of consuming meat and offal of such species has been found to be very low.